Pengaruh Remitansi Dan Variabel Makro Terhadap Perekonomian Indonesia Melalui Penyaluran Kredit Perbankan - Suryadi Suryadi (Jurnal Ketenagakerjaan, 2017)
Indonesia migrant worker (TKI) contributed to the country, through remittances. In addition to remittances, the phenomenon of inflation, interest rates, credit disbursement of the banking and economic growth had become a major issue in advancing the nation's economy. Based on this research, the relationship between the latent variable of remittances towards the latent variable of economic didn’t have any effect significantly. The latent variables of macro and credit, influenced the latent variable of economic significantly. The latent variable of macro had a significant and negative effect on the latent variables of credit and economic. The latent variable of credit was the biggest of its total effect on latent variable of economic with a value of0.934. The latent variable of remittances had total effect on the latent variable of economic amounted to 0.846 with the details of the direct effect of 0.014 and indirect effect of 0.832. The total effect for the latent variable of macro on the latent variable of economic amounted to -0.182 with details of the direct effect of -0.117 and indirect effect of -0.065 (-0.070 x 0.934).